Gentle Gestures of Control: On the Somatic Sensibilities of an IoT Remote App - Jūra Miniotaitė; Vaida Pakulytė; Ylva Fernaeus (Diseña, 2022)
The design of user experiences for physical appliances increasingly involves connection, monitoring, and control via smartphone applications. Despite the rich possibilities for interaction provided by smartphones, the current standard mode of engagement with such apps is through graphical user interface manipulations. To explore new felt experiences for this use context, a remote-control app for a robotic vacuum cleaner was designed, enabling participants to have their gaze focused on the robot, while steering it by gently tilting the phone. This particular interaction is used as a case to emphasize the role of somatic sensibilities when designing smartphone applications in the context of IoT. Through a phenomenologically-inspired analysis, we describe the user experience in terms of physical manipulation, perception, effort, and utility, and through social and emotional engagement. An important attribute was how the interaction, through its subtleness, created a somatically connected experience.